A Study Of Technology Acceptance Model (Tam) Towards Continuous Professional Development (Cpd) - Hashim, Norlezah; Idris, Fakrulradzi; Abu Talib, Noraini (2011)
The purpose of this project was to determine the technology acceptance using Technology Acceptance Model (TAM) towards Continuous Professional Development (CPD) system among University A academic staffs. The dependency of System Usage of CPD system as the dependent variable was cross check with four independent variables namely, Perceived Usefulness, Perceived Ease of Use, Management Support, and System Quality. A total of fifty five correspondents replied the questionnaires and the data obtained were analyzed using Statistical Package for the Social Quality have positive relationships with System Usage of CPD while management support has negative relationships with CPD.